Science of coercion communication research and psychological warfare, 1945 - 1960 - Simpson, Christopher (Oxford Univ. Press, 1994)
In this provocative study, Christopher Simpson demonstrates how the government-funded psychological warfare programs of the Cold War years underwrote the academic studies that formed the basis for much of modern communication research. U.S. psychological warfare programs in the Philippines, Middle East and Southeast Asia became essential in the creation and survival of what is widely considered to be mainstream mass communication studies. They aided in forming the widely held preconceptions that persist today in communication studies, public opinion research, and in the types of counterinsurgency operations that are today known as "public diplomacy" and "low intensity conflict." Science of Coercion: Communication Research and Psychological Warfare, 1945-1960 provides the first thorough examination of the role of the CIA, Pentagon, and other U.S. security agencies in the evolution of modern communication studies
Keywords: Geschichte 1945-1960; Communicatie; Communication - Recherche - États-Unis; Guerre froide; Guerre psychologique; Koude Oorlog; Onderzoek; Psychologische oorlogvoering; Kommunikation; Cold War; Communication -- Research -- United States; Psychological warfare; Psychologische Kriegführung; Kommunikationsforschung; États-Unis - Politique militaire; USA; United States -- Military policy